Bilingual education in China [ practices, policies, and concepts - Feng, Anwei , 1954- (Bilingual education and bilingualism ;, 2007)
Compares and contrasts two strands of bilingualism in China, one for minority nationality groups, the other for majority. This volume examines the history, policy, philosophy, politics, provision and